1994
DOI: 10.1155/1994/756247
|View full text |Cite
|
Sign up to set email alerts
|

Increased Frequency of the Uncommon Allele of a Tumour Necrosis Factor Alpha Gene Polymorphism in Rheumatoid Arthritis and Systemic Lupus Erythematosus

Abstract: The frequency of the uncommon allele (TNF2) of a polymorphism in the promoter region of the tumour necrosis factor alpha (TN Fα) gene in patients with rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) was found to be 3 times that of the normal anglo-saxon population. In SLE patients, this allele was strongly associated with HLA-DR3 expression and was also more frequent in patients who did not have malar rash. Functional studies of normal monocyte cytokine production in vitro showed that this gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
57
2
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 6 publications
(8 reference statements)
4
57
2
1
Order By: Relevance
“…Analysis of the transcrip- Table 8. Odds ratio of DRB1*03 stratified on TGF␤1 codon 10 for susceptibility to anti-SSB antibody in Sjögren's syndrome patients* TGF␤1 C positive (C/C ϩ C/T) TGF␤1 C negative (T/T) tional capacity and the functional relevance of this allele, which is usually associated with higher serum TNF values (27,28), is a subject of controversy, since a lack of association between TNF-308 polymorphisms and TNF␣ production has also been reported (29,30). A highly significant increase in the TNF2 allele frequency was observed only among patients with anti-SSB antibody, suggesting the role of anti-SSB in the association between TNF2 and primary SS.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the transcrip- Table 8. Odds ratio of DRB1*03 stratified on TGF␤1 codon 10 for susceptibility to anti-SSB antibody in Sjögren's syndrome patients* TGF␤1 C positive (C/C ϩ C/T) TGF␤1 C negative (T/T) tional capacity and the functional relevance of this allele, which is usually associated with higher serum TNF values (27,28), is a subject of controversy, since a lack of association between TNF-308 polymorphisms and TNF␣ production has also been reported (29,30). A highly significant increase in the TNF2 allele frequency was observed only among patients with anti-SSB antibody, suggesting the role of anti-SSB in the association between TNF2 and primary SS.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, functional studies of the allele À308A have been inconsistent, with both higher 30 and no change 31,32 in TNF-a production in cells stimulated with lipopolysaccharide. Studies using gene reporter assays have also shown effects ranging from increased 33 to no change 26,34 in gene transcription.…”
Section: Discussionmentioning
confidence: 99%
“…27 Another large Japanese study (n ¼ 387) looked at several TNF SNPs including À308, but only found that the T allele of the -857 SNP was increased in RA patients, and this link also proved to be dependent on HLA-DRB1*0405. 28 Perhaps, the most surprising finding is that while an Australian study 29 had reported an increase in the À308A allele in RA patients, two recent studies from Taiwan 30 and Sweden 31 reported an increased incidence of the À308G allele in RA patients, when compared to controls. In addition to studies of the incidence of RA, some researchers have examined the possible role of the allele variants in disease severity.…”
Section: Autoimmune Disease Associationsmentioning
confidence: 99%